Deep brain stimulation for dystonia. Issue 9 (15th November 2012) - Vidailhet, Marie; Jutras, Marie-France; Grabli, David; Roze, Emmanuel
Abstract : The few controlled studies that have been carried out have shown that bilateral internal globus pallidum stimulation is a safe and long-term effective treatment for hyperkinetic disorders. However, most recent published data on deep brain stimulation (DBS) for dystonia, applied to different targets and patients, are still mainly from uncontrolled case reports (especially for secondary dystonia). This precludes clear determination of the efficacy of this procedure and the choice of the 'good' target for the 'good' patient. We performed a literature analysis on DBS for dystonia according to the expected outcome. We separated those with good evidence of favourable outcome from those with less predictable outcome. In the former group, we review the main results for primary dystonia (generalised/focal) and highlight recent data on myoclonus-dystonia and tardive dystonia (as they share, with primary dystonia, a marked beneficial effect from pallidal stimulation with good risk/benefit ratio). In the latter group, poor or variable results have been obtained for secondary dystonia (with a focus on heredodegenerative and metabolic disorders). From this overview, the main results and limits for each subgroup of patients that may help in the selection of dystonic patients who will benefit from DBS are discussed.